Fractional killing arises from cell‐to‐cell variability in overcoming a caspase activity threshold. Issue 5 (7th May 2015) - Roux, Jérémie; Hafner, Marc; Bandara, Samuel; Sims, Joshua J; Hudson, Hannah; Chai, Diana; Sorger, Peter K
Abstract: When cells are exposed to death ligands such as TRAIL, a fraction undergoes apoptosis and a fraction survives; if surviving cells are re‐exposed to TRAIL, fractional killing is once again observed. Therapeutic antibodies directed against TRAIL receptors also cause fractional killing, even at saturating concentrations, limiting their effectiveness. Fractional killing arises from cell‐to‐cell fluctuations in protein levels (extrinsic noise), but how this results in a clean bifurcation between life and death remains unclear. In this paper, we identify a threshold in the rate and timing of initiator caspase activation that distinguishes cells that live from those that die; by mapping this threshold, we can predict fractional killing of cells exposed to natural and synthetic agonists alone or in combination with sensitizing drugs such as bortezomib. A phenomenological model of the threshold also quantifies the contributions of two resistance genes (c‐FLIP and Bcl‐2), providing new insight into the control of cell fate by opposing pro‐death and pro‐survival proteins and suggesting new criteria for evaluating the efficacy of therapeutic TRAIL receptor agonists. Synopsis: Non‐genetic cell‐to‐cell variability results in fractional killing by TRAIL and therapeutic antibody agonists, limiting their effectiveness as anti‐cancer drugs. A simple model of initiator caspase dynamics reveals a threshold in caspase activity that separates dying and surviving cells. A model of initiator caspase activity is predictive of fractional killing by TRAIL. The model identifies a caspase activity threshold that is constant across dose and type of agonist. Therapeutic antibodies targeting TRAIL receptors kill poorly because this threshold is not crossed. The caspase activity threshold and classic MOMP threshold interact to determine cellular sensitivity to apoptosis inducers. Abstract : Non‐genetic cell‐to‐cell variability results in fractional killing by TRAIL and therapeutic antibody agonists, limiting their effectiveness as anti‐cancer drugs. A simple model of initiator caspase dynamics reveals a threshold in caspase activity that separates dying and surviving cells.